2015
DOI: 10.1093/glycob/cwv102
|View full text |Cite
|
Sign up to set email alerts
|

Sweating the small stuff: Glycoproteins in human sweat and their unexplored potential for microbial adhesion

Abstract: There is increasing evidence that secretory fluids such as tears, saliva and milk play an important role in protecting the human body from infection via a washing mechanism involving glycan-mediated adhesion of potential pathogens to secretory glycoproteins. Interaction of sweat with bacteria is well established as the cause of sweat-associated malodor. However, the role of sweat glycoproteins in microbial attachment has received little, if any, research interest in the past. In this review, we demonstrate how… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 117 publications
1
15
0
Order By: Relevance
“…confirmed the presence of many glycoproteins, consistent with the results of previous analyses (Park et al, 2011;Peterson et al, 2016;Raiszadeh et al, 2012). The most abundant glycoproteins were Prolactin-inducible protein, Apolipoprotein D, Clusterin, Zinc alpha-2-glycoprotein, Immunoglobulin A1, and Cathepsin (Supplementary Table 1 provides the proteomic profiles of four typical sweat samples).…”
Section: Proteomic and Glycomic Profiles Of Sweatsupporting
confidence: 87%
See 1 more Smart Citation
“…confirmed the presence of many glycoproteins, consistent with the results of previous analyses (Park et al, 2011;Peterson et al, 2016;Raiszadeh et al, 2012). The most abundant glycoproteins were Prolactin-inducible protein, Apolipoprotein D, Clusterin, Zinc alpha-2-glycoprotein, Immunoglobulin A1, and Cathepsin (Supplementary Table 1 provides the proteomic profiles of four typical sweat samples).…”
Section: Proteomic and Glycomic Profiles Of Sweatsupporting
confidence: 87%
“…Sweat, the secretory fluid that regularly bathes human skin, provides some protection for the skin via at least components such as antimicrobial peptides and salts (Park et al, 2011). Our recent review (Peterson et al, 2016) has revealed that sweat also contains secreted glycoproteins that seem likely to play a role in providing molecular decoys for microbial adhesion as discovered in other…”
Section: Introductionmentioning
confidence: 99%
“…The exocytic mechanism mobilizes the cytoplasmic vesicles to sites on the plasma membrane, where the vesicular content is released to the extracellular space. On the other hand, the apical part of cells, at the apocrine sweat glands, are pinched off, leading to the release of the cytoplasm and cell membrane joined to the secretory materials (e.g., glycoproteins) [ 35 ]. Thus, the protein's partition rate into the sweat will be slower than ions.…”
Section: Sweat Gland Physiology and Web's Sweat Samplingmentioning
confidence: 99%
“…While more studies are necessary to determine the standard or basal levels of proteins in the sweat according to the activity level and the type of sweat gland that produces it, all the commented researches suggest that the ideal sweat sample should come from a unique type of sweat gland. The significant quantity of secreted sweat comes from eccrine glands [ 35 ], probably the best candidates to be tested.…”
Section: Sweat Gland Physiology and Web's Sweat Samplingmentioning
confidence: 99%
“…Alum (molecular formula: KAl(SO 4 ) 2 .12H 2 O) is a colourless, odorless crystalline solid that turns white in air [8]. The medical uses of alum in mouth rinses, vaccines development, haemostasis and inhibition of V. cholerae growth in water have been described [9][10][11][12]. However, to date there is no study on the effect of alum salt against bacterial skin flora.…”
Section: Introductionmentioning
confidence: 99%